Symptomatology associated with mental health disorders in health workers in Paraguay: COVID-19 effect - Samaniego, Antonio; Urzúa, Alfonso; Buenahora, Marcelo; Vera-Villarroel, Pablo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
COVID-19 disease has not only led to a collapse of the health system and the death of thousands of people but is also having an impact on the health of those who are providing care for those infected. In this context, the aim of this research was to determine prevalences of depression, anxiety, insomnia, distress and compassionate fatigue, as well as factors related to the presence of symptoms associated with these disorders in healthcare workers. For this, 126 health professionals from Paraguay were surveyed online, of which 83% were women, with an average age in the total sample of 32 years. The questionnaires PHQ-9 for depression, GAD-7 for anxiety, ISI-7 for insomnia, IES-R for distress and the module of compassion fatigue of ProQOL - CSF-vIV were applied. It was found that the percentages of participants who reported symptoms classified as moderate and severe were 32.2% for depression, 41.3% for anxiety, 27.8% for insomnia, 38.9% for distress and 64.3% for compassion fatigue. In addition, women and younger people were at greater risk for symptoms. The data provide evidence for the need to establish prevention or intervention strategies to cope with mental health problems in health professionals.